2017
DOI: 10.1177/1090198117728761
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Engagement Framework to Understand HPV Vaccination Among Latina and Vietnamese Women in a Planned Parenthood Setting

Abstract: Disparities in cervical cancer and human papillomavirus (HPV) vaccination persist among Vietnamese and Latina women. Through a partnership with Planned Parenthood of Orange and San Bernardino Counties (PPOSBC) in Southern California, we conducted in-depth interviews with young adult Latina (n = 24) and Vietnamese (n = 24) women, and PPOSBC staff (n = 2). We purposively sampled vaccinated women to elicit HPV vaccine decision narratives to uncover rich data on motivators, cultural values, and implicit vaccine at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 34 publications
1
46
0
Order By: Relevance
“…Campaign messages emphasized college students pursuing their interests and dreams with the time they gained from preventing HPV and HPV-related cancer. This approach aligns with current research that successful narrative messages depend on the perceived relevance of the storyline to the audience [ 31 , 48 ].…”
Section: Methodssupporting
confidence: 69%
“…Campaign messages emphasized college students pursuing their interests and dreams with the time they gained from preventing HPV and HPV-related cancer. This approach aligns with current research that successful narrative messages depend on the perceived relevance of the storyline to the audience [ 31 , 48 ].…”
Section: Methodssupporting
confidence: 69%
“…Twelve studies were conducted in the USA, three in the UK, one in the Netherlands, one in Denmark, one in Sweden, and one in Puerto Rico. Six studies were conducted in community organizations including faith-based centres like churches and mosques [21][22][23][24][25][26], eight in health and social service agencies [27][28][29][30][31][32][33][34], two in schools and/or community groups [35,36], another two in social clubs [37,38], and one in a household [39].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies revealed that some participants had not heard of HPV disease or HPV vaccine [27,33,35,39]. There were four studies that reported participants had no prior knowledge of HPV as a sexually transmitted disease or as a cause of cancer [25,30,32]. In four studies, participants described a lack of information and knowledge about the purpose of HPV vaccination, and HPV transmission [21,29,37].…”
Section: Resultsmentioning
confidence: 99%
“…To effectively reach young Latina and Vietnamese women with HPV vaccine prevention messages, source preferences should be considered (Hopfer, et al, 2017a(Hopfer, et al, , 2017b. Findings suggest that the use of many sources by Latina and Vietnamese women should inform dissemination strategies for the NCI EBCCP HPV Vaccine Decision Narratives.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention was originally developed to reach college women, and in the context of a randomized controlled trial the decision story messages nearly doubled vaccinations in the intervention relative to the control group (Hopfer, 2012). The EBCCP has since been adapted to reach many audiences, including women who seek care at safety-net clinics like Planned Parenthood (Hecht et al, 2021;Hopfer, Garcia, et al, 2017a;Hopfer Ray et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%